Adhesives based on butyl‐cyanoacrylate for fixation of autologous bone graft: Pilot study in rabbits. Issue 4 (5th May 2017) - Hochuli‐Vieira, Eduardo; Engler Pinto, Ana Carolina Basso; Pereira‐Filho, Valfrido Antonio; Saska, Sybele; Monnazzi, Marcelo Silva
Abstract: Background/Aim: Injuries to bone during trauma may require bone grafts and/or fixation to ensure optimal healing. Autologous bone grafts are still very common, but little data exist regarding the most effective means of fixation of such grafts. The aim of this study was to compare the fixation of autologous bone grafts with titanium screws and adhesives based on n ‐butyl‐cyanoacrylate. Material and Methods: Twenty adult rabbits were used. In group I, the graft was fixed with titanium screws (in one side of the animal head), while in groups II and III (in other spots in the same animal head), the graft was fixed with adhesive Tissuacryl® and Histoacryl®, respectively. The animals were sacrificed on post‐operative days 7, 15, 30, 60, and 120. Histological and histomorphometric analyses were performed. Results: Inflammatory reactions were observed in all groups at 7 days. At 15 days, group I showed no inflammatory reaction. There was new bone formation in group I at 30 days and at 60 days in groups II and III. After 120 days, the grafts were completely incorporated in group I and partially incorporated in groups II and III. Groups II and III presented less graft resorption at the final evaluation: 32.58 (±10.22) and 34.75 (±8.25), compared to 26.58 (±6.48) for group I ( P =.001). Conclusions: The adhesives were compatible when they were in contact with bone structures, and they were effective in fixing the grafts. Groups II and III had less graft resorption.